Antitumor and Apoptosis Induction Effects of Paeonol on Mice Bearing EMT6 Breast Carcinoma - Ou, Yetao (The Korean Society of Applied Pharmacology, 2014)
Paeonol is a major phenolic micromolecular component of Moutan cortex Radicis, a traditional Chinese Medicine. It has shown antitumor effects in previous studies; however, the underlying mechanisms remain unknown. This study investigated the mechanism by giving treatments of placebo, cyclophosphamide, paeonol of 150 and 300 mg/kg to 4 groups of mice bearing EMT6 breast cancer. Apoptosis in tumor cells were confirmed by morphology analysis, including hematoxylin, eosin staining and TUNEL staining. The results showed that the weight of EMT6 breast tumor was significantly reduced in the groups treated with both 150 and 300 mg/kg of paeonol. Immunohistochemical and Western blot results showed that the expression of Bcl-2 was down-regulated while the expression of Bax, caspase 8 and caspase 3 was up-regulated respectively. These results suggest that paeonol exhibits antitumor effects and the mechanism of the inhibition is via induction of apoptosis, regulation of Bcl-2 and Bax expression, and activation of caspase 8 and caspase 3.